2014
DOI: 10.1371/journal.pone.0096829
|View full text |Cite
|
Sign up to set email alerts
|

A Network Meta-Analysis of the Relative Efficacy of Treatments for Actinic Keratosis of the Face or Scalp in Europe

Abstract: BackgroundSeveral treatments are available for actinic keratosis (AK) on the face and scalp. Most treatment modalities were compared to placebo and therefore little is known on their relative efficacy.ObjectivesTo compare the different treatments for mild to moderate AK on the face and scalp available in clinical practice in Europe.MethodsA network meta-analysis (NMA) was performed on the outcome “complete patient clearance”. Ten treatment modalities were included: two 5-aminolaevulinic acid photodynamic thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 53 publications
2
93
1
11
Order By: Relevance
“…The included drugs comprised BF-200 ALA, ALA-patch, MAL, three modalities of imiquimod (3.75-5.0%), cryotherapy, 3% diclofenac in 2.5% hyaluronic acid, 0.5% 5-FU and ingenol mebutate. The metaanalysis indicates that all treatment options were significantly superior compared with placebo, with BF-200 ALA photodynamic therapy being the most efficient treatment [37]. This finding is corroborated by the findings of Dirschka et al who studied and compared 1 year follow-up treatments for selected AK treatment modalities and, among those, found BF-200 ALA to show the most sustainable efficacy [39].…”
Section: Photodynamic Therapy For Actinic Keratosismentioning
confidence: 63%
See 2 more Smart Citations
“…The included drugs comprised BF-200 ALA, ALA-patch, MAL, three modalities of imiquimod (3.75-5.0%), cryotherapy, 3% diclofenac in 2.5% hyaluronic acid, 0.5% 5-FU and ingenol mebutate. The metaanalysis indicates that all treatment options were significantly superior compared with placebo, with BF-200 ALA photodynamic therapy being the most efficient treatment [37]. This finding is corroborated by the findings of Dirschka et al who studied and compared 1 year follow-up treatments for selected AK treatment modalities and, among those, found BF-200 ALA to show the most sustainable efficacy [39].…”
Section: Photodynamic Therapy For Actinic Keratosismentioning
confidence: 63%
“…In clinical studies, PDT with aminolevulinic acid (ALA) has been shown to achieve good results within a short time and a maximum of two treatment sessions [37,38]. Several ALA-based topical medications have been used, mostly differing in regard to additional chemical modifications, other vehicle compositions, types of administration or the use of other wavelengths.…”
Section: Photodynamic Therapy For Actinic Keratosismentioning
confidence: 99%
See 1 more Smart Citation
“…7 This intraepidermal keratinocytic dysplasia may transform into invasive squamous cell carcinoma (SCC) in up to 20% within 10-25 years. 8 Although various therapy options exist, they often bear undesirable sideeffects. 7 To see whether CAP could be an effective therapy option, we treated seven patients (two females, five males) with Fitzpatrick skin types II or III and clinically diagnosed AK in this proof of concept study.…”
mentioning
confidence: 99%
“…27 Of 25 trials included, 18 were of topical treatments. Description of the regimens utilised was incomplete, but it appears that 12 trials corresponded to the treatments or formulations used in the UK.…”
Section: Comparative Efficacymentioning
confidence: 99%